Shrub ecosystem structure in response to anthropogenic climate change: A global synthesis - Wu, Zhehong; Wang, Wenzhi; Zhu, Wanze; Zhang, Peipei; Chang, Ruiying; Wang, Genxu (Science of The Total Environment, 2024)
Anthropogenic warming is predicted to alter ecological boundaries in energy-limited shrub ecosystems. Yet we still lack a sound understanding of the structural changes that shrub ecosystems are undergoing on a global scale and the factors driving them. To that end, here we collected studies of shrub dynamics from 227 sites worldwide to conduct a quantitative review, including the rate of advancing shrubline (their upslope shift), the rates of shrub cover and recruitment changes. Our results revealed that shrub expanded (e.g. shrubline shifts, shrub cover and recruitment increase) at the vast majority of sites (84 %); in contrast, they remained stable in 10 % of sites and descended at just 6 % of them. The mean global shift rate of shrubline was 1.22 m/year, being significantly faster in subarctic (> 60 degrees N) than temperate (< 60 degrees N) regions, and likewise more quickly in wet (total annual precipitation >400 mm) than dry (total annual precipitation <400 mm) areas; the annual change rates of shrub cover and recruitment increased by 0.89 % and 2.02 %. Shrubs communities have expanded rapidly in response to ongoing climate warming. The combination of autumn precipitation and winter temperature largely contributed to the general shift rates of shrubline, while the shrub cover and recruitment were mainly affected by summer temperature and precipitation in both spring and autumn. Furthermore, the site-specific pace of their expansion probably depends on a combination of local climatic and non-climatic drivers (such as fine-scale environmental conditions, disturbance, their interactions, and dispersal limitation). The increase of shrub distribution may alter the function and albedo of the ecosystems at high-latitude and -elevation regions, resulting in the feedback on climate.